2009
DOI: 10.1007/s10661-009-0798-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of remote sensing change detection techniques for assessing hurricane damage to forests

Abstract: This study compared performance of four change detection algorithms with six vegetation indices derived from pre- and post-Katrina Landsat Thematic Mapper (TM) imagery and a composite of the TM bands 4, 5, and 3 in order to select an optimal remote sensing technique for identifying forestlands disturbed by Hurricane Katrina. The algorithms included univariate image differencing (UID), selective principal component analysis (PCA), change vector analysis (CVA), and postclassification comparison (PCC). The indice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
59
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 39 publications
1
59
0
Order By: Relevance
“…These techniques are typically based on comparisons between data collected before and after a storm in the fallen area. Wang et al reported on the detection of downed trees in an affected area by comparing changes in optical remote sensing images and standard aerial photographs (4000-5000 m high) before and after a hurricane [6,7]. Szantoi et al employed a Sobel edge detection algorithm combined with spectral information based on color filtering.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques are typically based on comparisons between data collected before and after a storm in the fallen area. Wang et al reported on the detection of downed trees in an affected area by comparing changes in optical remote sensing images and standard aerial photographs (4000-5000 m high) before and after a hurricane [6,7]. Szantoi et al employed a Sobel edge detection algorithm combined with spectral information based on color filtering.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Lidar has been used to detect three-dimensional variance after hurricanes (Li et al 2008;Hussain et al 2011) and tornadoes (Kashani et al 2014). Texture information derived from imagery (Vijayaraj et al 2008;Radhika et al 2012) has been used to rapidly detect damaged areas, as have band ratios (e.g., Normalized Difference Vegetation Index; NDVI) (Ill et al 1997;Womble et al 2006;Liou et al 2010;Wang and Xu 2010;. Multi-temporal analysis is generally employed for postdisaster events through the application of change detection (Al-Khudhairy et al 2005;Chen & Hutchinson 2007, 2010Butenuth et al 2011) for coregistered pre-and post-event images.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the amount of time required to manually define the debris zone, there is much subjectivity in the delineation, and efforts to quickly establish a debris line or zone result in errors and oversimplification (Friedland et al 2011). Wang andXu (2010), , Thompson et al (2011), andSzantoi et al (2012) investigated detection of hurricane-damaged forest areas and forest debris, but automatic mapping of urban debris zones remains a research gap, particularly for events with widespread impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite image-based remote sensing has become an essential data source for assessing rapid or abrupt changes, being low cost, easily and readily accessible, yet it still provides adequate information (Kennedy et al 2009. A great variety of change detection approaches have been tested (Singh 1989, Coppin et al 2004, Kennedy et al 2009, McRoberts et al 2010, some of which have focused directly on the assessment of wind damage to forests (Wang & Xu 2010). In general, methodological approaches for detecting changes in vegetation can be grouped into two primary categories: trajectory analysis and bi-temporal methods (McRoberts & Walters 2012).…”
Section: Introductionmentioning
confidence: 99%